Neurocritical Care Organization in the Low-Income and Middle-Income Countries - Hemanshu, Prabhakar; Abhijit, V. Lele; Indu, Kapoor; Charu, Mahajan; Gentle S., Shrestha; Chethan, Venkatasubba Rao; Jose, I. Suarez; Sarah L., Livesay; Faraz, Shafq; Samuel Tsan, Ern Hung (Springer Nature and Neurocritical Care Society, 2025)
Background: This study aimed to assess the organization, infrastructure, workforce, and adherence to protocols in neurocritical care across low- and middle-income countries (LMICs), with the goal of identifying key gaps and oppor‑ tunities for improvement. Methods: We conducted a cross-sectional survey of 408 health care providers from 42 LMICs. The survey collected data on the presence of dedicated neurointensive care units, workforce composition, access to critical care technolo‑ gies, and adherence to evidence-based protocols. Data were analyzed using descriptive statistics, and comparisons were made across diferent geographical regions (East Asia and the Pacifc, Europe and Central Asia, Latin America and the Caribbean, the Middle East and North Africa, and South Asia and sub-Saharan Africa) and economic strata [lowincome countries (LICs), lower middle-income countries (LoMICs), and upper middle-income countries (UMICs)]. Results: Only 36.8% of respondents reported access to dedicated neurointensive care units: highest in the Middle East (100%), lowest in sub-Saharan Africa (11.5%), highest in LoMICs (42%), and lowest in LICs (13%). Access to critical care tech‑nologies, such as portable computed tomography scanners (9.3%; UMICs 11%, LICs 0%) and tele-intensive care unit services (14.9%; UMICs 19%, LICs 10%), was limited. Workforce shortages were evident, with many institutions relying on anesthesia residents for 24-h care. Adherence to protocols, including those for acute ischemic stroke (61.7%) and traumatic brain injury (55.6%), was highest in Latin America and the Caribbean (72% and 73%, respectively) and higher in UMICs (66% and 60%, respectively) but remained low in LICs (22% and 32%, respectively).